Development of Waste and Leftover Material Management System from Design Work: Pathway to Sustainable Faculty of Architecture - jantana, kantika; Jantana, Kwanchai (Journal of Faculty of Architecture and Design RMUTP, 2025)
This article presents an approach to develop a waste and leftover material management system for architectural and design education, responding to the demand of Rajamangala University of Technology Rattanakosin community, where 74.9% expressed the need for such a system in the 2020 survey. The research employs mixed methods, including surveys of waste quantity and types, stakeholder interviews, and case study analysis. The findings propose an integrated waste and material management system comprising four main components: (1) an efficient material sorting and storage system, (2) a material bank for design purposes in both physical and digital platform formats, (3) an upcycling promotion program, and (4) a collaboration network with communities and industries. The prototype system implementation results demonstrated significant waste reduction, cost savings, and carbon footprint reduction. Economic analysis shows that the system has a payback period of 3.26 years, an IRR of 24.76%, and generates a social return on investment (SROI) of 2.8 times.